Greco-Roman literature and the New Testament selected forms and genres - Aune, David Edward (Atlanta, GA Scholars, 1988)
Includes bibliographical references.
Keywords: Bible. N.T. -- criticism, form; Greek literature, Hellenistic -- history and criticism; Literary form